The problem of high water cut in the products of horizontal wells - K. O. Shcherbakova (Известия высших учебных заведений: Геология и разведка)
Background. The production of oil and gas by horizontal wells, despite all its advantages, is subject to exploratory and operational complications. At the final stage of their development, such fields become hard-to-recover reserves. Production of oil and gas is often associated with a high water cut, a significant drop in reservoir pressure, and precipitation of asphaltene deposits.Aim. To analyze the problem of early indication of flooding of horizontal wells and do research on existing solutions nowadays.Materials and methods. The dependence of the logarithm of the water-oil ratio on the cumulative oil production was investigated. An analysis of production decline curves was carried out, along with a graphical diagnostics of flooding evolution.Results. The anticipated cumulative production of a well was determined by continuing the linear dependence to its economic limit. A graph was plotted in semi-logarithmic coordinates for the analysis of production decline curves. According to the dependence of the water-oil ratio versus time, the type of early well flooding was determined in logarithmic coordinates.Conclusion. One of the most significant problems in the development of horizontal wells consists in the high water cut of the obtained products. According to the data for 2020, the average water cut in the main fields of Russia comprises at least 85%, with the mass ratio of produced oil and associated water approaching 1:7. The use of water-soluble polymers for waterproofing of horizontal wells can be considered a promising direction due to their efficiency in limiting water inflow in vertical and directional wells.